The Effect of Speed On Bow Thruster Tunnel Acoustics Using Computational Fluid Dynamics Methods - Dedy Wahyudi; Ardan Nagra Coutsar; Dian Prasetyawati; Putro Adi Nugroho (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2025)
The increasing global emphasis on sustainability and environmental conservation has driven the maritime industry to adopt technologies aimed at minimizing ecological impacts, particularly underwater noise pollution. As a significant environmental issue, underwater noise affects marine ecosystems, altering the behavior, physiology, and survival of marine fauna, while contributing to broader ecological shifts. This research investigates the acoustic properties of a vessel's bow thruster tunnel, focusing on noise generation at varying operational speeds. The study utilizes Computational Fluid Dynamics (CFD) simulations with ANSYS Fluent to analyze the relationship between fluid flow and acoustic behavior within the tunnel. Simulations conducted using CFD ANSYS Fluent reveal that high acoustic concentrations occur at the tunnel due to significant pressure differences between the interior and exterior. Results show that acoustic levels increase with ship velocity, ranging from 81.39 dB at 10 knots to 108.86 dB at 28 knots. To mitigate noise, a cone ring inlet design is proposed to reduce pressure differences and the ship's acoustic signature. These findings underscore the importance of vessel speed in influencing underwater noise levels, which can affect operational efficiency, marine ecosystems, and ship performance. The study highlights the need for a multi-faceted approach, incorporating hull design, propulsion systems, and operational strategies, to minimize acoustic impacts and promote sustainable maritime practices.